Therapeutic functions of medical implants from various material categories with integrated biomacromolecular systems - Calais, Guilherme Bedeschi; Garcia, Guilherme Domingos; de Moura Júnior, Celso Fidelis; Soares, José Diego Magalhães; Lona, Liliane Maria Ferrareso; Beppu, Marisa Masumi; Hernandez-Montelongo, Jacobo; Rocha Neto, João Batista Maia (Frontiers in Bioengineering and Biotechnology, 2025)
Medical implants are designed to replace missing parts or improve body functions and must be capable of providing structural support or therapeutic intervention for a medical condition. Advances in materials science have enabled the development of devices made from metals, polymers, bioceramics, and composites, each with its specific advantages and limitations. This review analyzes the incorporation of biopolymers, proteins, and other biomacromolecules into implants, focusing on their role in biological integration and therapeutic functions. It synthesizes advancements in surface modification, discusses biomacromolecules as carriers for controlled drug release, and explores the application of nanoceramics and composites to improve osseointegration and tissue regeneration. Biomacromolecule systems are capable of interacting with device components and therapeutic agents - such as growth factors (GFs), antibiotics, and nanoceramics - allowing control over substance release. Incorporating therapeutic agents into these systems enables localized treatments for tissue regeneration, osseointegration, post-surgery infection control, and disease and pre-existing conditions. The review highlights these materials’ therapeutic advantages and customization opportunities, by covering mechanical and biological perspectives. Developing composites and hybrid drug delivery systems align with recent efforts in interdisciplinary personalized medicine and implant innovations. For instance, a trend was observed for integrating inorganic (especially nanoceramics, e.g., hydroxyapatite) and organic phases in composites for better implant interaction with biological tissues and faster recovery. This article supports understanding how integrating these materials can create more personalized, functional, durable, and biocompatible implant devices.